Retrospective Analysis of Adoptive TIL Therapy plus Anti-PD1 Therapy in Patients with Chemotherapy-Resistant Metastatic Osteosarcoma - Xiang Zhou; Junlong Wu; Chunguang Duan; Yingjie Liu (Journal of Immunology Research)
Background. The pathological subtype of osteosarcoma is one of the most common malignant bone tumors. Notably, chemotherapy-resistant metastatic osteosarcoma has been reported to cause significant mortality and shows poor prognosis with the currently available multidisciplinary treatments. This study investigated whether combined adoptive TIL and anti-PD1 therapy improves the prognosis of patients with chemotherapy-resistant metastatic osteosarcoma. Methods. A total of 60 patients with chemotherapy-resistant metastatic osteosarcoma between June 2016 and March 2018 were enrolled. The primary endpoint was to evaluate the safety and adverse effects (AEs) of infusions of TIL and anti-PD1 therapy in the patients. Besides, secondary endpoints included assessing the objective response rate (ORR), progression-free survival time (PFS), and overall survival time (OS). Results. We reported that combined TIL therapy and anti-PD1 therapy is safe and all treatment-related AEs were reversible or manageable. The ORR of all the patients is 36.67%, and patients with more infusions of TIL and CD8+TIL, less infusions of CD8+PD1+TIL, and less infusion of CD4+FoxP3+TIL exhibited increased PFS and OS. Conclusion. This study determined that combined TIL and anti-PD1 therapy is safe and effective in metastatic osteosarcoma patients with chemotherapy resistance.